THE EFFECTIVENESS OF USING NATURE ANIMAL DOCUMENTARY VIDEO ON STUDENT’S ABILITY IN LEARNING VOCABULARY AT ELEVENTH GRADE - Siregar, Elvi Dayanti (Faculty of Tarbiyah nad Teacher Training, 2021)
The aim of this research is to find out the effect of using nature animal documentary video on students’ ability in Learning Vocabulary at tenth grade students of Mas Darul Qura’an Amplas. In this research, the researcher use the quantitative research with the a quasi-exprimental design.The sample of the research was 50 students. There are 25 students from MIA-2 as exprimental class and there are 25 students from IIS-1 as control class. The writer teach the experimental group by using nature animal documentary video and the control class without using nature animal documentary video. In control class, the researcher used the media ppt. The result of the research was significant with the average scores of exprimental class were 55,6 for the pre-test and 81 for the post-test, then the average scores for the control class were 53,4 for the pre-test and 74,8 for the post-test. The researcher found that the mean scores in the exprimental class was higher than the control class scores (81> 74,8). The t-test results also shows that t-observed (2,8) was higher than t- table at a significance level of 5% (0,05) with 48 degrees of freedom of 2,063. The result of the calculation showed that the statistic data of both showed that t-observed was higher than t-table (2,8 > 2,063 p = 0.05). It means that Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. The calculation was showed that there is a significant effect of using animal documentary video on student’s ability in learning vocabulary. Keywords : Vocabulary, Student’s Ability and Nature Animal Documentary Video.